Chronic pancreatitis - Forsmark, Christopher (Henry Stewart Talks, 2011)
Multiple predisposing conditions with a final common pathway of fibrosis, Smoking and alcohol are well known major risk factors, recently identified conditions include autoimmune pancreatitis and genetic forms of pancreatitis, Diagnosis is straightforward in patients with far-advanced disease, and quite challenging and difficult in those with early disease, Treatment of pain, Treatment of Exocrine insufficiency, Complications